Real-world glycemic outcomes in patients with type 2 diabetes initiating exenatide once weekly and liraglutide once daily: a retrospective cohort study - Saunders WB (Dove Medical Press, 2016)
William B Saunders,1 Hiep Nguyen,2 Iftekhar Kalsekar2 1Department of Public Health Sciences, College of Health and Human Services, The University of North Carolina at Charlotte, Charlotte, NC, 2AstraZeneca, Fort Washington, PA, USA Aim: The glucagon-like peptide-1 receptor agonists exenatide once weekly (QW) and liraglutide once daily (QD) have demonstrated improvements in glycemic outcomes in patients with type 2 diabetes mellitus in randomized clinical trials. However, little is known about their real-world comparative effectiveness. This retrospective cohort study used the Quintiles Electronic Medical Record database to evaluate the 6-month change in glycated hemoglobin (A1C) for patients initiating exenatide QW or liraglutide QD.Methods: Patients with type 2 diabetes mellitus prescribed exenatide QW (n=664) or liraglutide QD (n=3,283) between February 1, 2012 and May 31, 2013 were identified. Baseline A1C measures were from 75 days before to 15 days after initiating exenatide QW or liraglutide QD, with follow-up measures documented at 6 months (±45 days). Adjusted linear regression models compared the difference in mean A1C change. A priori defined sensitivity analysis was performed in the subgroup of patients with baseline A1C ≥7.0% and no prescription for insulin during the 12-month pre-index period.Results: For exenatide QW and liraglutide QD, respectively, mean (SD) age of the main study cohort was 58.01 (10.97) and 58.12 (11.05) years, mean (SD) baseline A1C was 8.4% (1.6) and 8.4% (1.6), and 48.2% and 54.2% of patients were women. In adjusted models, change in A1C did not differ between exenatide QW and liraglutide QD during 6 months of follow-up. Results were consistent in the subgroup analyses.Conclusion: In a real-world setting, A1C similarly improves in patients initiating exenatide QW or liraglutide QD. Keywords: diabetes, exenatide, outcomes